Pengaruh Campuran Limbah Cucian Beras Dan Air Kelapa Terhadap Pertumbuhan Tanaman Sawi Hijau (Brassica Juncea L.) - Simbolon, Veronika Amelia; Samosir, Kholilah; Erda, Gustriza; Rahmi, Afrilia (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
The characteristics of the soil in the Tanjungpinang City area have a low level of fertility, so in this case many farmers use soil fertilizing substances in the form of inorganic fertilizers, where the farmers assume that the use of inorganic fertilizers can speed up the planting period and increase crop yields, without knowing the impact of applying inorganic fertilizers directly. Continuously and in excessive doses can cause physical damage to the soil. Soil damage due to the use of inorganic fertilizer can be avoided by changing inorganic fertilizer to organic fertilizer, where organic fertilizer can quickly overcome nutrient deficiencies, does not damage soil humus and dissolves easily in the soil and carries important nutrients for soil fertility. The aim of the research was to determine the nutrient content (N-Total, P2O5, K2O, Mg, Ca) in a mixture of rice washing waste and coconut water with concentrations of 50%, 75% and 100% on the growth of green mustard plants. The type of research used is a quantitative approach, experimental method with a Complete Randomized Block Design (CRBD) using a 2 x 3 factorial pattern with 3 repetitions. The type of data analysis used in this research is ANOVA (Off Variance Analysis) and further test Tukey. The results of the research showed that the concentration that had the best growth effect on all parameters was a concentration of 50% with the result being an average stem height of 6.845 cm, average leaf width of 2.918 cm and an average number of leaves of 5.8644 pieces. It was concluded that each concentration had a significantly different effect on the growth of mustard green plants and the most influential in the growth of mustard green plants was the 50% concentration.